Ankieter w terenie, problemy z jakością badań ilościowych = The interviewer in the field, problems with the quality of quantitative research - Lisowski, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article focuses on the issues of deliberate violations of procedures for field by interviewers. These issues are not often taken in methodological studies due to financial difficulties of data availability. Even if all parties involved in the research process are aware of the existence of the problem, they are not interested in airing it, fearing a negative impact on the image of the research industry (branch). The consideration focuses on the description of the most commonly fraud interviewers and analysis of control procedures in order to prevent them. Another attempt is to indicate the factors related to the functioning of the research industry that can have an impact on the frequency of unfair practices.
Keywords: jakość badań ilościowych; ankieter; oszustwa ankieterskie; kontrole badań terenowych; prestiż zawodu ankietera; the quality of quantitative research; the interviewer; fraud interviewer; inspections of field research; the prestige of the profession interviewer